Reducing the breeding success of Canada and Greylag Geese, Branta canadensis and Anser anser, on gravel pits - Wright, R M; Phillips, V E (Wildfowl, 1991)
The numbers of nesting pairs of Canada and Greylag Geese have increased steadily at the gravel pits at Great Linford and it has become necessary to attempt to limit population growth because of local agricultural damage. In 1990 gosling production was reduced by removing 817 eggs from 89 Canada and 50 Greylag nests. In the first 12 days of the nesting season, the removal of complete clutches from 58 nests of marked Canada Goose pairs resulted in 80% of the geese re-laying and, of these replacement clutches, 95% were incubated. First clutches removed after this period resulted in 21% of pairs re-laying and only 28% of these were incubated. The clutches of unmarked pairs were replaced by two hard-boiled or wooden eggs in an attempt to prevent re-laying. Seventy-two percent of Canada Goose pairs incubated the substitute eggs for a mean of 38 days; 52% of the Greylag Goose pairs incubated these eggs for a mean of 26 days. Normal incubation period is approximately 28 days for both species. Production from 72 nests with substitute eggs was only one Canada gosling. From these two experiments, it was concluded that a successful strategy for control through egg removal is to place substitute eggs in the nests of early laying pairs. Few geese nesting later will re-lay and incubate their second clutch.